Kinerja Dinas Kesehatan dalam Menekan Angka Stunting di Kabupaten Bangli - BG, Dev Nandini; Purnamaningsih, Putu Eka; Yasintha, Putu Nomy (CITIZEN CHARTER, 2022)
Bangli Regency has high stunting cases in Bali Province, based from RISKESDAS (National Basic Health Research) 2018, Bangli Regency was declared to have a stunting prevalence of 43.2%. In its efforts to deal with it, the Bali Provincial Government has set Bangli Regency as the locus of stunting reduction in Bali in 2020. Therefore, the Bangli Regency Government through the Office of Bangli Public Health continue to improving their performance in reducing stunting rates in Bangli. The purpose of this study is to find out about the performance of the Office of Bangli Public Health in reducing stunting rates in Bangli Regency according to the Ministerial Regulation of health of the Republic Indonesia number 29 of 2019.The indicator that we used to define the Performance of the Office of Bangli Public Health Service in reducing stunting in Bangli is the performance measurement of Dwiyanto (2006) there are Productivity, Service Quality, Responsiveness, Responsibility and Accountability. The research method used in this research is descriptive qualitative, datas were collected by observation, interviews, and documentation studies. The results showed that the performance of the Office of Bangli Public Health in suppressing the stunting rate in Bangli was still not fully optimal. There are still deficiencies that cause the stunting reduction efforts is hampered, such as the lack of nutrition workers, budget limitation, the lack of additional food for stunting children and the lack of socialization regarding the function of iron tablets for young women in Bangli Regency. Keywords: Performance, Suppressing, Stunting